Design and Implementation of a Reservation System and a New Queuing for Remote Labs - Khazri, Yassine; Fahli, Ahmed; Moussetad, Mohamed; Naddami, Ahmed (International Journal of Online and Biomedical Engineering (iJOE), 2019)
Remote laboratories are important in education because they provide access to equipment that some institutions cannot afford to purchase or maintain, reduce the need for dedicated physical space for equipment and personnel to staff laboratories. But more than just fill the absence of real physical laboratories; remote laboratories can improve the users experience through the use of adaptive and specific. An important element in supporting shared access is coordinating the scheduling of the laboratory usage. Optimized scheduling can significantly decrease access waiting times and improve the utilization level of remote laboratories resources, with associated reductions in per-use costs. The user management systems that exist so far are limited, and not compatible with all remote lab interface development software. For that, we worked on the development of a new user management system for remote laboratories. This paper proposes a model and set of diagrams that define the new reservation system and a new Queuing for remote laboratories for educational purposes.